The outlaw of Sherwood Forest - Seven, John (Seven, John. Time-tripping Faradays, 2015)
Their latest adventure takes teenagers Dawkins and Hypatia back to thirteenth-century Nottingham and Sherwood Forest, but when they find a time-traveling device in a cave they find themselves far in the future--and closer to the forces that are tampering with time.